METHODS OF IMAGING IN THE DIAGNOSIS OF TEMPOROMANDIBULAR JOINT DISORDERS - Tvrdy, Petr (Biomedical papers, 2007)
Background: Different methods of temporomandibular joint imaging are presented and discussed. Research reports published from 1979 to 2002 have been evaluated. Method and Results: The aim of this paper is to summarize the main findings from research. Basic X-ray examination is the most readily available method of imaging which usually does not have any contraindication. The use of computer tomography offers all advantages of tomographic scanning in different layers and projections, imaging soft tissues close to the joint and the possibility of "3D" reconstruction of bone structures. In case of joint dysfunctions and internal joint derangement, it is more preferable to use nuclear magnetic resonance for the depiction of the joint structures. To make a diagnosis more efficient, miniinvasive diagnostic methods are becoming necessary. Arthroscopy allows direct visual control of the joint space with the possibility of therapeutic help in cases when conservative treatment has failed. Ultrasonography, as a completely non-invasive procedure, is applied even in diagnosing functional temporomandibular defects. In these cases the diagnostic value of ultrasonography is almost comparable with this of nuclear magnetic resonance.Conclusions: So it is possible that, together with the improvement of the equipment, development of the diagnostic methods used during the treatment of temporomandibular joint defects could continue in this direction.
Keywords: Temporomandibular joint/Methods of imaging/Examinations